A animação educativa no desenvolvimento pessoal e social de futuros formadores: uma abordagem centrada na prática teatral - Maria José dos Santos Cunha (Universidade do Minho, 2008)
In this article, based on a study developped in extra-curricular context with preservice kindergarten and elementary school teachers, we intend to focus on the role of a still ill-explored issue in the context of initial formation, the theme of educational animation, combined with theatrical practice. The process that lead to it is briefly described, the results are presented and its values are discussed accordingly